Distillers’ Grains Peptides Scavenge Free Radicals and Influence Volatile Compounds of Chi-Aroma Baijiu - Renjie Zhang; Xi Hu; You Luo; Siqin Zheng; Zhenqiang Wu (Applied Sciences, 2024)
The production of Chi-aroma Baijiu generates free radicals, which may pose potential health risks. This study aimed to scavenge free radicals in Chi-aroma Baijiu and assess the impact on the composition of volatile compounds (VOCs) by using distillers’ grains-derived homologous peptides. Five peptides—Pro-Ala (PA), Pro-Val (PV), Gly-Leu (GL), Asp-Phe (DF), and Pro-Leu (PL)—were isolated from the distillers’ grain filtrate. These peptides are present in trace amounts in Chi-aroma Baijiu. By supplementing five peptides to Chi-aroma Baijiu, they could completely scavenge hydroxyl radicals. The rate of scavenging alkoxy radicals ranged from 10.84% to 35.66%. Furthermore, these peptides had an impact on ethyl nonanoate, diethyl acetal, and octanal, which were recognized as characteristic compounds. Ultraviolet spectroscopy simulation revealed that the highest absorption peaks of certain peptides shift when they interact with various esters. Those peptides interact with ethyl acetate and ethyl lactate via hydrogen bonding and Van der Waals forces, demonstrating their influence on VOCs. These findings offer new insights into free radical scavenging, flavor compound regulation, and the valorization of Baijiu by-products in Chi-aroma Baijiu production.